High-temperature-oxidation-resistant expandable graphite and preparation process thereof

By mixing phosphate and modified nano-attapulgite composite antioxidant with expandable graphite, a dense structure is formed, which solves the problem of expandable graphite being easily oxidized at high temperatures, achieves structural and performance stability at high temperatures, and is suitable for high-temperature harsh working conditions.

CN120622483APending Publication Date: 2025-09-12CHANGYI SENHUI NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511036146.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-26
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Expandable graphite is easily oxidized in high-temperature environments, resulting in structural collapse, decreased physical strength and sealing barrier properties, limiting its application in high-temperature and harsh working conditions.

Method used

A composite of phosphate and modified nano-attapulgite is used as an antioxidant, mixed with expandable graphite, and formed into a dense structure through a cake pressing process to inhibit oxidation reaction.

Benefits of technology

It significantly inhibits the oxidation of expandable graphite at high temperatures, maintains stable structure and performance, and is suitable for high-temperature and harsh working conditions in aerospace, metallurgy, chemical industry, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005518788620000091
    Figure BDA0005518788620000091
  • Figure BDA0005518788620000101
    Figure BDA0005518788620000101
Patent Text Reader

Abstract

The invention relates to the technical field of graphite processing, and particularly discloses high-temperature-oxidation-resistant expandable graphite and a preparation process thereof. The preparation process of the high-temperature-oxidation-resistant expandable graphite comprises the following steps: mixing and stirring graphite and an intercalator to react, washing, carrying out suction filtration, and drying to obtain a first solid; an antioxidant is added into the first solid according to the mass ratio of 1: (0.004-0.01), precipitation is performed after mixing, a second solid is obtained, the antioxidant comprises phosphate and modified nano attapulgite, then the second solid is expanded at the temperature of 900-1000 DEG C, and the composite material is obtained after cake pressing. The high-temperature-oxidation-resistant expandable graphite can be used in the field of high-temperature sealing barrier materials, has the advantage of excellent high-temperature-oxidation-resistant performance, is low in thermal weight loss rate and ash content, and has excellent compression resilience.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of graphite processing, and more specifically, to a high-temperature oxidatively resistant expandable graphite and a preparation process thereof. Background Art

[0002] Expandable graphite (EG) is an important engineering material. It uses strong oxidants (such as concentrated sulfuric acid, nitric acid, and potassium permanganate) to intercalate graphite layers, forming a graphite intercalation compound with a unique layered structure. The intercalation compound rapidly decomposes and vaporizes at high temperatures, generating a tremendous expansion force that causes the graphite particles to expand significantly along the C-axis, forming a worm-like expanded graphite. This expanded graphite exhibits unique properties such as excellent expandability, high flexibility, low density, good thermal and electrical conductivity, and chemical stability. It is widely used in sealing materials, fire retardants, electromagnetic shielding materials, and high-temperature insulation materials.

[0003] However, although expandable graphite has many advantages, due to the insufficient intrinsic high-temperature oxidation resistance of its carbon structure, expandable graphite easily undergoes oxidation reaction with oxygen in high-temperature environment, causing its structural collapse. For expandable graphite, oxidation damages its interlayer structure, making it unable to effectively expand or its expansion ratio drops sharply when heated. For expanded graphite, oxidation catalyzes and pulverizes its flexible worm structure, losing its original physical strength and sealing barrier properties, and its thermal and electrical conductivity also decreases significantly. This not only significantly shortens the service life of the material, but also easily causes safety hazards, seriously restricting the application of expandable graphite in high-temperature and harsh working conditions such as aerospace, metallurgy, and chemical industry.

[0004] To improve the oxidation resistance of expandable graphite, existing technologies typically employ methods such as doping with non-carbon elements, coating the surface with inorganic coatings, and impregnating with various oxidant systems. Regarding these related technologies, the inventors discovered that while these existing technologies improve expandable graphite's oxidation resistance, they also generally compromise the carbon content of the material, sacrificing its inherent properties, such as electrical and thermal conductivity, expansion properties, and high flexibility. Summary of the Invention

[0005] In order to improve the high-temperature oxidation resistance of expandable graphite and at the same time improve the physical strength and sealing barrier properties of expandable graphite, the present application provides a high-temperature oxidation-resistant expandable graphite and a preparation process thereof.

[0006] In a first aspect, the present application provides a process for preparing high-temperature oxidatively expandable graphite, which adopts the following technical solution: A preparation process of high-temperature oxidation-resistant expandable graphite comprises the following steps: S1: mixing graphite and a first intercalant in a mass ratio of 1:(2-8) to obtain a mixture, adding the mixture to a second intercalant and stirring to react, washing, filtering, separating, and drying at 100-180° C. to obtain a first solid; S2: adding an antioxidant to the first solid at a mass ratio of 1:(0.004-0.01), mixing and then precipitating to obtain a second solid; S3: expanding the second solid at 900-1000° C. and pressing the solid into a cake to obtain; The antioxidant includes phosphate and modified nano-attapulgite.

[0007] By adopting the above technical solution, the inventors found that by using a composite of phosphate and modified nano-attapulgite as an antioxidant and mixing it with expandable graphite in a mixed manner, an addition amount of only 0.4-1% can significantly inhibit the oxidation of expandable graphite at high temperatures, and the thermal weight loss rate and ash content are both low, so that the expandable graphite maintains stable structure and performance at high temperatures.

[0008] Phosphates can dehydrate and polymerize at high temperatures to form metaphosphates or polyphosphates, forming a dense glassy or crystalline protective layer on the surface of expandable graphite, covering the active sites at the graphite edges and inhibiting the starting point of oxidation. Modified nano-attapulgite, with its nanoscale particle size and porous tubular structure, can penetrate the gaps between the worms in expandable graphite, forming a micro-skeleton support network that bridges adjacent graphite worms, significantly improving the graphite's pulverization and separation at high temperatures. It also creates a maze effect within the expandable graphite, tortuously extending the propagation paths of oxygen and heat, significantly reducing oxygen permeability and oxygen attack sites. Working in synergy with phosphates, it effectively inhibits the occurrence of high-temperature oxidation reactions, ensuring the high-temperature structural stability and mechanical properties of the expandable graphite.

[0009] This application immediately compresses the expandable graphite into a cake after high-temperature expansion, allowing it to form a more densely packed structure in the semi-molten state of the worms, achieving densification and reducing porosity. Compared to expandable graphite that has not undergone the cake-pressing process, this structure not only helps improve the graphite's ability to resist external pressure and impact, but also reduces the path of oxygen and heat conduction, reducing the possibility of oxidation reactions. Furthermore, the antioxidant forms a protective layer on the graphite surface. The cake-pressing process optimizes the graphite's microstructure, making the protective layer more uniform and stable, significantly improving the expandable graphite's high-temperature oxidation resistance under high-temperature conditions.

[0010] Optionally, the mass ratio of the phosphate to the modified nano-attapulgite is 1:(0.21-0.37).

[0011] By adopting this technical solution, when the modified attapulgite ratio is less than 0.21, the cross-linked network formed by the nano-attapulgite is sparse, and the phosphate glass phase is susceptible to cracking due to thermal stress. However, when the ratio exceeds 0.37, the overfilling of the nano-attapulgite may inhibit graphite expansion, resulting in adverse effects. At a ratio of 0.21-0.37 in the present application, the chemical barrier provided by the phosphate glass phase and the physical support provided by the attapulgite fibers complement each other, achieving excellent high-temperature oxidation resistance with a relatively low addition amount.

[0012] Optionally, the preparation process of the modified nano-attapulgite comprises the following steps: S1: Ultrasonic dispersion of nano-attapulgite in an ethanol solution to form a suspension, adding a silane coupling agent to a concentration of 3-5 wt %, adjusting the pH to 4.5-5, refluxing at 75-85° C., centrifuging, washing, and drying to obtain pretreated nano-attapulgite; S2: adding the pretreated nano-attapulgite to the amino-modified graphene suspension, adjusting the pH to 8-8.5, heating and stirring, centrifuging, washing and drying to obtain the modified nano-attapulgite.

[0013] Optionally, in step S2, the mass ratio of the pretreated nano-attapulgite to the aminated graphene in the aminated graphene suspension is 1:(0.05-0.25).

[0014] Optionally, the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

[0015] By adopting the above technical solution, γ-glycidyloxypropyltrimethoxysilane is used as a silane coupling agent, and the water structure can form a Si-O-Al covalent bond with the hydroxyl group on the surface of the nano-attapulgite, while retaining the terminal epoxy group, thereby enhancing the wettability between the nano-attapulgite and graphite.

[0016] Furthermore, by using amino graphene, a stable chemical bond can be formed on the surface of nano-attapulgite through a ring-opening reaction between amino groups and epoxy groups in an alkaline environment, thereby further improving the wettability to graphite, so that the nano-attapulgite is evenly dispersed and anchored in the expandable graphite system and is not easy to fall off. The two-dimensional sheets of amino graphene and the one-dimensional structure of attapulgite are further interwoven into a network, thereby enhancing the ability of expandable graphite to block oxygen penetration. At the same time, the thermal stability and resilience of the amino graphene on the surface of the modified nano-attapulgite are also enhanced, so that its decomposition temperature can adapt to the expansion temperature of expandable graphite, thereby reducing the loss of intrinsic performance.

[0017] In addition, amino graphene may release high nitrogen-containing gas to dilute the oxygen concentration under high temperature conditions, and the residual carbon layer can cover the surface of expandable graphite, further blocking oxygen and inhibiting the oxidation of graphite edges, ensuring the various performances of expandable graphite under high temperature.

[0018] Optionally, the phosphate is a composite phosphate comprising aluminum phosphate and magnesium phosphate in a mass ratio of (2-7):1.

[0019] By adopting the above technical solution, the composite phosphate formed by aluminum phosphate with a high melting point and magnesium phosphate with low-temperature melting properties can effectively resist high-temperature oxidation of expandable graphite in a wider temperature range.

[0020] Optionally, the first intercalant is 98% concentrated sulfuric acid, and the second intercalant is 25% hydrogen peroxide.

[0021] In a second aspect, the present application provides a high-temperature oxidation-resistant expandable graphite, which is prepared by a preparation process of the high-temperature oxidation-resistant expandable graphite of the present application.

[0022] In a third aspect, the present application provides an application of high-temperature oxidation-resistant expandable graphite in the field of high-temperature sealing barrier materials.

[0023] By adopting the above-mentioned technical solution, the expandable graphite prepared by the preparation process of the present application can maintain good high-temperature oxidation stability under high-temperature working conditions of 670°C, has a low thermal weight loss rate and a low ash content, and maintains the good physical strength and sealing barrier properties of the expandable graphite, making the expandable graphite more suitable for application in high-temperature and harsh working conditions such as aerospace, metallurgy, and chemical industry.

[0024] In summary, this application has the following beneficial effects: 1. Since the present application adopts an antioxidant formed by a composite of phosphate and nano-attapulgite, the phosphate is dehydrated and polymerized at high temperature to form a dense glassy protective layer, covering the active sites on the edge of the graphite. The nano-attapulgite, through its nano-particle size and porous tubular structure, is interspersed in the worm gaps of the expandable graphite to form a micro-skeleton support network, while tortuously extending the propagation path of oxygen and significantly reducing the oxygen permeability. The antioxidant synergistically formed by the two is mixed with the expandable graphite in a mixed manner and then combined with the cake pressing process. Only 0.4-1% of the addition amount can achieve significant inhibition of the oxidation of the expandable graphite at high temperature, and the thermal weight loss rate and ash content are low, so that the expandable graphite maintains stable structure and performance at high temperature.

[0025] 2. In this application, it is preferred to use γ-glycidyloxypropyltrimethoxysilane to modify the nano-attached attapulgite and then attach amino graphene to the surface of the nano-attached attapulgite. This not only enhances the wettability of the nano-attached attapulgite to graphite, but also further interweaves the two-dimensional sheets of amino graphene with the one-dimensional structure of the attapulgite into a network, further enhancing the ability of the expandable graphite to block oxygen penetration. At the same time, it also enhances the thermal stability and resilience of the amino graphene on the surface of the modified nano-attached attapulgite, so that its decomposition temperature can adapt to the expansion temperature of the expandable graphite, thereby reducing the loss of intrinsic performance.

[0026] 3. The expandable graphite prepared by the preparation process of the present application can maintain good high-temperature oxidation stability under high-temperature conditions of 670°C, has a low thermal weight loss rate and a low ash content, and maintains the good physical strength and sealing barrier properties of the expandable graphite, making the expandable graphite more suitable for applications in high-temperature and harsh working conditions such as aerospace, metallurgy, and chemical industry. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below with reference to the following examples and comparative examples. Unless otherwise specified, the raw materials used in the examples and comparative examples of the present invention are all commercially available products.

[0028] Preparation example of modified nano-attapulgite Preparation Example 1 Modified nano-attapulgite is obtained by modifying nano-attapulgite with a silane coupling agent and amino graphene, wherein the nano-attapulgite is in the form of nanorod crystals with a purity of ≥99%, a diameter of 10-30 nm, and a length of 800-1000 nm; the amino graphene is amino-modified single-layer graphene with a nitrogen content of 25-30 wt% and a particle size of 180-300 nm. The preparation process comprises the following steps: S1: adding the nano-attapulgite to a 90% ethanol solution at a material-liquid ratio of 1:20 and ultrasonically dispersing it for 20 minutes to form a suspension, adding γ-glycidyloxypropyltrimethoxysilane so that the concentration of γ-glycidyloxypropyltrimethoxysilane is 3 wt%, adjusting the pH to 4.5 with hydrochloric acid, refluxing at 85°C for 2 hours, centrifuging, washing with anhydrous ethanol three times, and then vacuum drying at 60°C for 8 hours to obtain pretreated nano-attapulgite; S2: Add the aminated graphene to water and ultrasonically disperse it for 30 minutes to prepare a 1.2 wt% aminated graphene suspension. Add the pretreated nano-attapulgite to the aminated graphene suspension, wherein the mass ratio of the pretreated nano-attapulgite to the aminated graphene is 1:0.017. Adjust the pH to 8 with ammonia water, stir at 80°C for 14 hours, centrifuge, wash with deionized water 3 times, and then vacuum dry at 50°C for 10 hours to obtain modified nano-attapulgite.

[0029] Preparation Example 2 The modified nano-attapulgite is different from that in Preparation Example 1 in that its preparation process includes the following steps: S1: adding nano-attapulgite to a 90% ethanol solution at a material-liquid ratio of 1:20 and ultrasonically dispersing for 20 minutes to form a suspension, adding γ-glycidyloxypropyltrimethoxysilane to make a concentration of γ-glycidyloxypropyltrimethoxysilane of 5wt%, adjusting the pH to 5 with hydrochloric acid, refluxing at 75°C for 4 hours, centrifuging, washing with anhydrous ethanol three times, and then vacuum drying at 60°C for 8 hours to obtain pretreated nano-attapulgite; S2: Add the aminated graphene to water and ultrasonically disperse it for 30 minutes to prepare a 1.2 wt% aminated graphene suspension. Add the pretreated nano-attapulgite to the aminated graphene suspension, wherein the mass ratio of the pretreated nano-attapulgite to the aminated graphene is 1:0.017. Adjust the pH to 8 with ammonia water, stir at 80°C for 14 hours, centrifuge, wash with deionized water 3 times, and then vacuum dry at 50°C for 10 hours to obtain modified nano-attapulgite.

[0030] Preparation Example 3 The modified nano-attapulgite is different from that in Preparation Example 1 in that its preparation process includes the following steps: S1: adding nano-attapulgite to a 90% ethanol solution at a material-liquid ratio of 1:20 and ultrasonically dispersing for 20 minutes to form a suspension, adding γ-glycidyloxypropyltrimethoxysilane to make a concentration of γ-glycidyloxypropyltrimethoxysilane of 5wt%, adjusting the pH to 5 with hydrochloric acid, refluxing at 80°C for 3 hours, centrifuging, washing with anhydrous ethanol three times, and then vacuum drying at 60°C for 8 hours to obtain pretreated nano-attapulgite; S2: Add the aminated graphene to water and ultrasonically disperse it for 30 minutes to prepare a 1.2wt% aminated graphene suspension. Add the pretreated nano-attapulgite to the aminated graphene suspension, wherein the mass ratio of the pretreated nano-attapulgite to the aminated graphene is 1:0.017. Adjust the pH to 8.5 with ammonia water, stir at 80°C for 12 hours, centrifuge, wash with deionized water three times, and then vacuum dry at 50°C for 10 hours to obtain modified nano-attapulgite.

[0031] Preparation Example 4 The modified nano-attapulgite is different from that in Preparation Example 1 in that its preparation process includes the following steps: S1: adding nano-attapulgite to a 90% ethanol solution at a material-liquid ratio of 1:20 and ultrasonically dispersing for 20 minutes to form a suspension, adding γ-glycidyloxypropyltrimethoxysilane to make a concentration of γ-glycidyloxypropyltrimethoxysilane of 4 wt%, adjusting the pH to 4.5 with hydrochloric acid, refluxing at 80° C. for 4 hours, centrifuging, washing with anhydrous ethanol three times, and then vacuum drying at 60° C. for 8 hours to obtain pretreated nano-attapulgite; S2: Add the aminated graphene to water and ultrasonically disperse it for 30 minutes to prepare a 1.2 wt% aminated graphene suspension. Add the pretreated nano-attapulgite to the aminated graphene suspension, wherein the mass ratio of the pretreated nano-attapulgite to the aminated graphene is 1:0.017. Adjust the pH to 8 with ammonia water, stir at 80°C for 14 hours, centrifuge, wash with deionized water 3 times, and then vacuum dry at 50°C for 10 hours to obtain modified nano-attapulgite.

[0032] Preparation Example 5 The modified nano-attapulgite is different from Preparation Example 1 in that the mass ratio of the pretreated nano-attapulgite to the aminated graphene in the aminated graphene suspension is 1:0.05, and the other steps are the same as Preparation Example 1.

[0033] Preparation Example 6 The modified nano-attapulgite is different from Preparation Example 1 in that the mass ratio of the pretreated nano-attapulgite to the aminated graphene in the aminated graphene suspension is 1:0.25, and the other steps are the same as Preparation Example 1.

[0034] Preparation Example 7 The modified nano-attapulgite differs from Preparation Example 1 in that the process of step S2 is not performed. Specifically, the nano-attapulgite is added to a 90% ethanol solution at a material-liquid ratio of 1:20 and ultrasonically dispersed for 20 minutes to form a suspension, γ-glycidyloxypropyltrimethoxysilane is added to make the concentration of γ-glycidyloxypropyltrimethoxysilane be 3wt%, the pH is adjusted to 4.5 with hydrochloric acid, refluxed at 85°C for 2h, centrifuged, washed with anhydrous ethanol 3 times, and then vacuum dried at 60°C for 8h. Example

[0035] Example 1 A preparation process of high-temperature oxidation-resistant expandable graphite comprises the following steps: S1: Natural flake graphite and 98% concentrated sulfuric acid were mixed in a mass ratio of 1:3 and stirred for 30 min to obtain a blend; S2: adding hydrogen peroxide with a mass concentration of 25% to the blend, stirring at 50° C. for 30 min, wherein the amount of hydrogen peroxide added is 10% of the mass of the graphite, washing with deionized water 5 times for 10 min each time after solid-liquid separation, filtering and separating, and drying at 160° C. to constant weight to obtain a first solid; S3: adding an antioxidant to the first solid material in a mass ratio of 1:0.008, mixing and precipitating to obtain a second solid material; the antioxidant is a phosphate and modified nano-attapulgite in a mass ratio of 1:0.21, the phosphate is aluminum phosphate and magnesium phosphate in a mass ratio of 2:1, and the modified nano-attapulgite is obtained by Preparation Example 1; S4: The second solid material is fully expanded at 980° C. and pressed into a cake to obtain high-temperature oxidatively resistant expandable graphite.

[0036] Example 2 A preparation process of high-temperature oxidation-resistant expandable graphite comprises the following steps: S1: Natural flake graphite and 98% concentrated sulfuric acid were mixed in a mass ratio of 1:2 and stirred for 40 min to obtain a blend; S2: adding hydrogen peroxide with a mass concentration of 25% to the blend, stirring at 50° C. for 30 min, wherein the amount of hydrogen peroxide added is 10% of the mass of the graphite, washing with deionized water 5 times for 10 min each time after solid-liquid separation, filtering and separating, and drying at 160° C. to constant weight to obtain a first solid; S3: adding an antioxidant to the first solid material in a mass ratio of 1:0.008, mixing and precipitating to obtain a second solid material; the antioxidant is a phosphate and modified nano-attapulgite in a mass ratio of 1:0.28, the phosphate is aluminum phosphate and magnesium phosphate in a mass ratio of 4:1, and the modified nano-attapulgite is obtained by Preparation Example 2; S4: Expand the second solid at 900° C. and press into a cake to obtain high-temperature oxidatively resistant expandable graphite.

[0037] Example 3 A preparation process of high-temperature oxidation-resistant expandable graphite comprises the following steps: S1: Natural flake graphite and 98% concentrated sulfuric acid were mixed in a mass ratio of 1:6 and stirred for 25 min to obtain a blend; S2: adding hydrogen peroxide with a mass concentration of 25% to the blend, stirring at 50° C. for 30 min, wherein the amount of hydrogen peroxide added is 10% of the mass of the graphite, washing with deionized water 5 times for 10 min each time after solid-liquid separation, filtering and drying at 180° C. to constant weight to obtain a first solid; S3: adding an antioxidant to the first solid material in a mass ratio of 1:0.008, mixing and precipitating to obtain a second solid material; the antioxidant is a phosphate and modified nano-attapulgite in a mass ratio of 1:0.33, the phosphate is aluminum phosphate and magnesium phosphate in a mass ratio of 5.5:1, and the modified nano-attapulgite is obtained by Preparation Example 3; S4: Expand the second solid at 1000° C. and press into a cake to obtain high-temperature oxidatively resistant expandable graphite.

[0038] Example 4 A preparation process of high-temperature oxidation-resistant expandable graphite comprises the following steps: S1: Natural flake graphite and 98% concentrated sulfuric acid were mixed in a mass ratio of 1:8 and stirred for 20 min to obtain a blend; S2: adding hydrogen peroxide with a mass concentration of 25% to the blend, stirring at 50° C. for 30 min, wherein the amount of hydrogen peroxide added is 10% of the mass of the graphite, washing with deionized water 5 times for 10 min each time after solid-liquid separation, filtering and drying at 100° C. to constant weight to obtain a first solid; S3: adding an antioxidant to the first solid material in a mass ratio of 1:0.008, mixing and precipitating to obtain a second solid material; the antioxidant is a phosphate and modified nano-attapulgite in a mass ratio of 1:0.37, the phosphate is aluminum phosphate and magnesium phosphate in a mass ratio of 7:1, and the modified nano-attapulgite is obtained by Preparation Example 4; S4: Expand the second solid at 950° C. and press into cakes to obtain high-temperature oxidatively resistant expandable graphite.

[0039] Example 5 A high-temperature oxidation-resistant expandable graphite is different from Example 1 in that, in step S3 of its preparation process, the mass ratio of prefabricated expandable graphite to antioxidant is 1:0.004, and the other steps are the same as Example 1.

[0040] Example 6 A high-temperature oxidation-resistant expandable graphite is different from Example 1 in that, in step S3 of its preparation process, the mass ratio of prefabricated expandable graphite to antioxidant is 1:0.01, and the other steps are the same as Example 1.

[0041] Example 7 A high-temperature oxidation-resistant expandable graphite is different from Example 1 in that the modified nano-attapulgite in the antioxidant in step S3 of its preparation process is prepared by Preparation Example 5, and the other steps are the same as Example 1.

[0042] Example 8 A high-temperature oxidation-resistant expandable graphite is different from Example 1 in that the modified nano-attapulgite in the antioxidant in step S3 of its preparation process is prepared by Preparation Example 6, and the other steps are the same as Example 1.

[0043] Example 9 A high-temperature oxidation-resistant expandable graphite is different from Example 1 in that the modified nano-attapulgite in the antioxidant in step S3 of its preparation process is prepared by Preparation Example 7, and the other steps are the same as Example 1.

[0044] Example 10 A high-temperature oxidation-resistant expandable graphite is different from Example 1 in that the phosphate in the antioxidant in step S3 of its preparation process is only magnesium phosphate, and the other steps are the same as Example 1.

[0045] Example 11 A high-temperature oxidation-resistant expandable graphite is different from Example 1 in that the phosphate in the antioxidant in step S3 of its preparation process is only aluminum phosphate, and the other steps are the same as Example 1.

[0046] Comparative Example Comparative Example 1 A high-temperature oxidation-resistant expandable graphite is different from Example 1 in that, in step S3 of its preparation process, the mass ratio of prefabricated expandable graphite to antioxidant is 1:0.002, and the other steps are the same as Example 1.

[0047] Comparative Example 2 A high-temperature oxidation-resistant expandable graphite is different from Example 1 in that, in step S3 of its preparation process, the mass ratio of prefabricated expandable graphite to antioxidant is 1:0.015, and the other steps are the same as Example 1.

[0048] Comparative Example 3 A high-temperature oxidation-resistant expandable graphite, which differs from Example 1 in that the modified nano-attapulgite in the antioxidant in step S3 of the preparation process is replaced by unmodified nano-attapulgite of equal mass, and the other steps are the same as Example 1.

[0049] Comparative Example 4 A high-temperature oxidation-resistant expandable graphite is different from Example 1 in that the modified nano-attapulgite in the antioxidant in step S3 of the preparation process is replaced by phosphate of equal mass, and the other steps are the same as Example 1.

[0050] Comparative Example 5 A high temperature oxidation resistant expandable graphite is different from Example 1 in that no antioxidant is added, and other steps are the same as Example 1.

[0051] Performance testing The following relevant performance test tests were performed on the high temperature oxidation resistant expandable graphite obtained by the preparation processes of Examples 1-11 and Comparative Examples 1-5, and the final results are recorded in Table 1.

[0052] 1. Weight loss rate: Weigh (1.1 ± 0.1) g of the high-temperature oxidation-resistant expandable graphite obtained after pressing the cakes in Examples 1-11 and Comparative Examples 1-5, respectively, place them in a muffle furnace at 670°C, oxidize them at this temperature for 4 hours, and weigh them after cooling. Calculate the weight loss rate of each group of samples. Each group of tests was performed three times, and the average of the three results was taken as the final result. Weight loss rate (%) = (initial mass of sample - residual mass after oxidation) / initial mass of sample × 100%; 2. Ash content: Weigh (1.1 ± 0.1) g of the high-temperature oxidatively expandable graphite obtained by pressing the cakes in Examples 1-11 and Comparative Examples 1-5, respectively. Spread the sample in a crucible using a combustion method and calcine at a constant temperature of (900 ± 25) ° C for 2 h to completely release the graphite component and the volatile component. After cooling, weigh the residue mass and calculate the ash content of each group of samples. Each group of tests was performed 3 times, and the average of the 3 results was taken as the final result. Ash content (%) = mass of the residue after calcination / initial mass of the sample × 100%. The lower the ash content, the higher the fixed carbon content of the high-temperature oxidatively expandable graphite. 3. Compression and Rebound Performance: The high temperature oxidation-resistant expandable graphites obtained in Examples 1-11 and Comparative Examples 1-5 were stacked to a thickness of 1.8 mm. An initial load was applied and maintained for 15 seconds under a temperature of 23° C. and a relative humidity of 55%. The sample thickness was recorded as P0. The main load was then applied slowly and uniformly to the total load and maintained for 60 seconds. The sample thickness was recorded as P1. The main load was immediately removed and maintained for 60 seconds. The thickness P2 of the sample under the original load was recorded as the rebound thickness. Three different points were measured for each group of samples, and the arithmetic mean of the three different points was taken as the compression and rebound of the expandable graphite: compression (%) = (P0-P1) / P2×100%; rebound (%) = (P2-P1) / (P0-P1)×100%.

[0053] Table 1 According to the performance test results of Examples 1-4, Examples 7-8 and Comparative Examples 4-5 in Table 1, the expandable graphite prepared by the preparation process of high-temperature oxidation-resistant expandable graphite of the present application has excellent high-temperature oxidation resistance, and the thermal weight loss rate under high-temperature conditions of 670°C is 0.88-2.29%, and the ash content is 1.22-1.32%.

[0054] This shows that the present application uses an antioxidant formed by a composite of phosphate and nano-attapulgite, and the two are synergistically mixed with expandable graphite in a mixed manner, and then combined with a cake pressing process. Only 0.4-1% of the antioxidant added can significantly inhibit the oxidation of expandable graphite at high temperatures, significantly improve the antioxidant properties of expandable graphite while ensuring the carbon content is qualified, and maintain the stability of the intrinsic properties.

[0055] Furthermore, it can be seen that the addition of nano-modified attapulgite not only helps to improve the antioxidant properties of expandable graphite, but also further improves the compression resilience of expandable graphite. This is because the two-dimensional sheets of amino graphene and the one-dimensional structure of attapulgite are further interwoven into a network, which enhances the ability of expandable graphite to block oxygen penetration. At the same time, it also optimizes the network structure inside the expandable graphite, making the expandable graphite have good compression resilience properties. When used as a raw material for sealing barrier materials, it can be more suitable for high-temperature and harsh working conditions in aerospace, metallurgy, chemical industry, etc.

[0056] In Examples 10-11, only a single type of phosphate is used as the antioxidant component, and the thermal weight loss rate is increased. The high-melting point aluminum phosphate and the low-melting magnesium phosphate composite as phosphate can more effectively inhibit oxidation in a wider temperature range.

[0057] According to the performance test results of Example 1, Example 9 and Comparative Example 3, it can be seen that the modified nano-attached attapulgite obtained by attachment modification with a silane coupling agent and amino-modified graphene, when mixed with an antioxidant and expandable graphene, significantly enhances the wettability of the nano-attached attapulgite on graphite, compared with the unmodified nano-attached attapulgite in Comparative Example 3 and the nano-attached attapulgite modified only with a silane coupling agent in Example 9, so that the nano-attached attapulgite can be evenly dispersed inside the expandable graphite, significantly enhancing the ability of the expandable graphite to block oxygen penetration and the performance of the compressed micro-elastics, and the two-dimensional sheets of the amino-modified graphene and the one-dimensional structure of the nano-attached attapulgite are further interwoven into a network, which further improves the compression rebound properties of the expandable graphite.

[0058] Unmodified nano-attapulgite is prone to agglomeration or uneven dispersion when mixed with expandable graphite, resulting in limited improvement in the antioxidant properties of expandable graphite and a high thermal weight loss rate.

[0059] According to the performance test results of Example 1, Examples 5-6 and Comparative Examples 1-2, it can be seen that the antioxidant in the present application is only added in an amount of 0.4-1% to achieve significant inhibition of the oxidation of expandable graphite at high temperatures, and the thermal weight loss rate and ash content are both low, so that the expandable graphite maintains stable structure and performance at high temperatures. When the addition amount is less than 0.4%, the high-temperature oxidation inhibition effect of the expandable graphite is effective, the thermal weight loss rate is high, and it can maintain good high-temperature oxidation stability under high-temperature conditions of 670°C. It has a low thermal weight loss rate and a low ash content, and maintains the good physical strength and sealing barrier properties of the expandable graphite. When the addition amount is greater than 1%, the high-temperature oxidation inhibition effect of the expandable graphite is not further improved, but the ash content is increased, resulting in a decrease in carbon fixation, and the intrinsic properties of the expandable graphite are affected.

[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A process for preparing high temperature resistant oxidation expandable graphite, characterized in that: The following steps are involved: S1: mixing graphite and a first intercalant in a mass ratio of 1:(2-8) to obtain a mixture, adding the mixture to a second intercalant and stirring to react, washing, filtering, separating, and drying at 100-180° C. to obtain a first solid; S2: adding an antioxidant to the first solid at a mass ratio of 1:(0.004-0.01), mixing and then precipitating to obtain a second solid; S3: expanding the second solid at 900-1000° C. and pressing the solid into a cake to obtain; The antioxidant includes phosphate and modified nano-attapulgite.

2. The preparation process of high temperature resistant oxidation expandable graphite according to claim 1, characterized in that: The mass ratio of the phosphate to the modified nano-attapulgite is 1:(0.21-0.37).

3. The preparation process of high temperature resistant oxidation expandable graphite according to claim 1, characterized in that, The preparation process of the modified nano-attapulgite comprises the following steps: S1: Ultrasonic dispersion of nano-attapulgite in an ethanol solution to form a suspension, adding a silane coupling agent to a concentration of 3-5 wt %, adjusting the pH to 4.5-5, refluxing at 75-85° C., centrifuging, washing, and drying to obtain pretreated nano-attapulgite; S2: adding the pretreated nano-attapulgite to the amino-modified graphene suspension, adjusting the pH to 8-8.5, heating and stirring, centrifuging, washing and drying to obtain the modified nano-attapulgite.

4. The process for preparing high temperature resistant oxidation expandable graphite according to claim 3, wherein: In step S2, the mass ratio of the pretreated nano-attapulgite to the aminated graphene in the aminated graphene suspension is 1:(0.05-0.25).

5. The process for preparing high temperature resistant oxidation expandable graphite according to claim 3, wherein: The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.

6. The process for preparing high temperature resistant oxidation expandable graphite according to claim 1, wherein: The phosphate is a composite phosphate, comprising aluminum phosphate and magnesium phosphate in a mass ratio of (2-7):

1.

7. The process for preparing high temperature resistant oxidation expandable graphite according to claim 1, wherein: The first intercalant is 98% concentrated sulfuric acid, and the second intercalant is 25% hydrogen peroxide.

8. A high temperature oxidation resistant expandable graphite, prepared by the process for preparing the high temperature oxidation resistant expandable graphite according to any one of claims 1 to 7.